Effects of eccentric preloading on concentric vertical jump performance in youth athletes - Gillen, Z. M.; Jahn, L. E.; Shoemaker, M. E.; McKay, B. D.; Mendez, A. I.; Bohannon, N. A.; Cramer, J. T. (Journal of Applied Biomechanics, 2019)
This study measured peak force (PF), peak rate of force development (PRFD), peak power (PP), concentric impulse, and eccentric impulse during static jump (SJ), countermovement jump (CMJ), and drop jump (DJ) in youth athletes to examine changes in vertical jump power with progressively greater eccentric preloading in relation to age, maturity, and muscle mass. Twenty-one males ranging from 6 to 16 years old performed the following vertical jumps in a random order: SJ, CMJ, and DJ from drop heights of 20, 30, and 40 cm (DJ20, DJ30, and DJ40, respectively). Measurements included PF, PRFD, PP, eccentric impulse, and concentric impulse for each vertical jump condition. Maturity offset was calculated, while ultrasound images quantified thigh muscle cross-sectional area (CSA). PF and PRFD increased from CMJ to DJ20. PP increased from SJ to CMJ. Concentric impulse remained unchanged, but eccentric impulse increased systematically from across jumps. The change in PP from SJ to CMJ was correlated with age, height, weight, maturity offset, and CSA. The CMJ resulted in the greatest concentric PP with the least amount of eccentric preloading. The inability of young athletes to translate the energy absorbed during the eccentric phase of the stretch-shortening cycle of DJs may be influenced by growth and development.